Edible insects as alternative food for human - TURAN, YAVUZ; SESAL, NÜZHET CENK (My University, 2023)
According to international institutions, a rapidly increasing population and the emergence of food shortages have led people to seek alternative food. Because meat consumption will increase many times in the future, plants, mycoproteins, seaweeds and insects that attract the most attention and interest are the alternative protein sources. The amount of protein contained in insects, along with oil, energy, mineral values, etc. the fact that it has a rich nutritional content has caused insects to come to the fore as an alternative food source. Not only in terms of nutritional value, but also the ease of production and time saving show that the sustainability of insects is higher than other traditional foods. Although edible insects are not widespread all over the world, it does not seem like a dream that they will be in the first place among alternative food sources in the future. With this review, valuable information will be given about insects as an alternative food source, and information will be shared about the sustainability of insects as a food source in the future.
Keywords: edible insects; entomophagy; insect protein; sustainable nutrition; gastronomy